2012
DOI: 10.1016/j.yqres.2012.05.015
|View full text |Cite
|
Sign up to set email alerts
|

Lacustrine records of Holocene flood pulse dynamics in the Upper Paraguay River watershed (Pantanal wetlands, Brazil)

Abstract: The Pantanal is the world's largest tropical wetland and a biodiversity hotspot, yet its response to Quaternary environmental change is unclear. To address this problem, sediment cores from shallow lakes connected to the Upper Paraguay River (PR) were analyzed and radiocarbon dated to track changes in sedimentary environments. Stratal relations, detrital particle size, multiple biogeochemical indicators, and sponge spicules suggest fluctuating lake-level lowstand conditions between ~ 11,000 and 5300 cal yr BP,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
69
0
9

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 68 publications
(86 citation statements)
references
References 66 publications
(70 reference statements)
8
69
0
9
Order By: Relevance
“…This is entirely consistent with diatom and sediment chemistry data for this period and with changes in the species of Pediastrum found in the core. It is also consistent with the reconstruction of McGlue et al (2012) for the period between 9000 and 6200 cal a BP, although we see no evidence for their proposed mid Holocene (6200 to 5300 cal a BP) lake expansion.…”
Section: Comparison With Other Published La Gaiba Recordssupporting
confidence: 89%
See 2 more Smart Citations
“…This is entirely consistent with diatom and sediment chemistry data for this period and with changes in the species of Pediastrum found in the core. It is also consistent with the reconstruction of McGlue et al (2012) for the period between 9000 and 6200 cal a BP, although we see no evidence for their proposed mid Holocene (6200 to 5300 cal a BP) lake expansion.…”
Section: Comparison With Other Published La Gaiba Recordssupporting
confidence: 89%
“…There is a delay between peak summer rainfall and peak water levels in the Pantanal (when the Paraguay River and its associated lakes overflow), which increases from north to south across the wetlands. In the central wetlands (including La Gaiba) this delay is several months (Alho, 2005;McGlue et al, 2012). Studies of precipitation, discharge in the Paraguay River and inundation area of the wetlands (Hamilton, 2002;Alho, 2005) have confirmed that there is a clear relationship between precipitation amount (monsoon strength) and water levels in the Pantanal wetlands and lakes, hence lake level variations in La Gaiba can be taken as being indicative of broad scale precipitation changes associated with changes in the SASM.…”
Section: Study Sitementioning
confidence: 99%
See 1 more Smart Citation
“…This lake has yielded long-term palaeoclimate records, inferred from reconstructed lake-level changes [19][20][21] and pollen-based vegetation reconstructions [22,23]. These records indicate that eastern Chiquitanía and the Pantanal have rstb.royalsocietypublishing.org Phil.…”
Section: Study Site and Methodsmentioning
confidence: 92%
“…Available pollen records from several sites in the southern Amazon Basin point to drier conditions during the last glacial period (Mayle et al 2000;Burbridge et al, 2004), suggesting a disconnect between the interior tropics and other regions. Several recent studies have focused on reconstructing hydrologic conditions in the Pantanal, a large wetland expanse primarily located in the Mato Grosso do Sul region of Brazil and roughly equidistant between the well-studied Central Andes and southern Brazil regions (Metcalfe et al, 2014;Whitney et al, 2011;Whitney and Mayle, 2012;McGlue et al, 2012). Evidence from pollen, diatoms and other biological proxies in a continuous ~45,000-year sediment record from Laguna La Gaiba (LLG) suggest drier and cooler conditions in the Pantanal during the last glacial period (Metcalfe et al, 2014;Whitney et al, 2011).…”
Section: Introductionmentioning
confidence: 99%